Loon Copter: Implementation of a hybrid unmanned aquatic–aerial quadcopter with active buoyancy control - Alzu'bi, Hamzeh; Mansour, Iyad; Rawashdeh, Osamah (Journal of field robotics, 2018)
Aquatic–aerial unmanned vehicles recently became the focus of many researchers due to their various possible applications. Achieving a fully operational vehicle that is capable of aerial, water‐surface, and underwater operations is a significant challenge considering the vehicle's air–water–air transition, propulsion system, and stability underwater. We present in this paper an unconventional unmanned hybrid aquatic–aerial quadcopter with active buoyancy control that is capable of aerial flight and water‐surface operation, as well as subaquatic diving. We report on the first successful prototype of the vehicle, named the Loon Copter, to provide initial evaluation results of its performance in both mediums. The Loon Copter uses a single set of motors and propellers for both air and underwater maneuvering. It utilizes a ballast system to control vehicle buoyancy and depth underwater, as well as to perform seamless air‐to‐water and water‐to‐air transitions. A closed loop control algorithm is utilized for the vehicle's aerial and water‐surface stability and maneuver, whereas an open loop control algorithm is used for underwater maneuver. The experimental results show a fully operational prototype with six degrees of freedom underwater, stable flight, operation capabilities on water surface, and agile maneuvering underwater.